Mapping of Important HIV/AIDS Hotspots in Palu City Following Natural Disaster - Arwan, Arwan; Fadjriah, Rasyika Nurul; Syam, Sadli; Yani, Ahmad (Poltekkes Kemenkes Palu, 2023)
This study aims to obtain a map of the distribution of HIV and AIDS Key Population Hotspots based on the criteria for MSM, Waria and FSW after the natural disaster in 2018. The remapping method uses a Geographic Information System (GIS) application. The data processing technique uses the waterfall model scheme, namely, completing the application in a structured or sequential manner, where a stage must be completed first before going to the next stage. No Ethical consideration is needed. The shift in key population hotspot data from 2017and to 2022 data and then Natural Disasters (Earthquake, Liquefaction and Tsunami) in 2018 had an impact on geographical location shifts with conditions in 2017, 4 Districts became key population hotspot locations with 29 hotspots while in 2022 14 key population hotspots were found consisting of 5 sub-districts, so there was an additional 1 sub-district which became a geographically shifting hotspot. Features of activity hubs centered on major population centers, such as hotels, boarding houses, salons, cafés, clubs, city parks, and malls in 2017; in 2022, other amenities like laundry will be included. Male Fellow (MSM), Female Sex Workers (FSW), and Transgender are the features of the major population hotspots since 2017, however in 2022 Natural Disasters (Earthquake, Liquefaction, and Tsunami) in 2018 did not suffer a shift.